Baromfitrágya alapú komposzt szuszpenzió hatásának vizsgálata káposzta (Brassica oleracea L. convar. capitata provar. capitata Dutch) tesztnövénnyel - Gorliczay, Edit; Kiss, Nikolett Éva; Nagy, Attila; Tamás, János (GEORGIKON FOR AGRICULTURE, 2022)
Compost teas are watery extracts of composted materials that are used to control plant diseases and on crop fertilization. In this work, we tested the nutrient replenishment effect of a broiler and hen manure-based non-aerated compost tea on two soil types (Arenosol, slightly humous Arenosol), with cabbage (Brassica oleracea L. convar. capitata provar. capitata Dutch) as a test plant, at one water capacity level (Field Capacity 70 w/w%), with harvesting times of four and eight weeks. The trends in leaf number, wet weight (g), total length (cm), Fv/Fm, Fv/Fo, total chlorophyll (μg/g) and total carotenoids (μg/g) were investigated. Based on the results of the pot experiments, significant differences (p<0.05) were observed between the control and compost suspension treated plants in terms of the parameters studied and harvest times. The treatments resulted in a higher number of leaves, and this strong foliage growth is probably the result of nitrogen overdose. Fv/Fm and Fv/Fo were determined to determine the stress on the plants, which indicated that high potassium concentrations affected the photosynthetic apparatus. For total chlorophyll and carotenoid content (μg/g), lower values were measured for plants treated with suspensions, which can be explained by antagonism between potassium and magnesium ions.